"Let Them Eat Stuffed Peppers": An Argument of Images on the Role of Food in Understanding Neoliberal Austerity in Greece - Sutton, David (Gastronomica, 2016)
This paper focuses on how discourses of food have shaped understandings of what is at stake in the Greek crisis. Drawing from Karl Polanyi's concept of "embeddedness," I argue that food is central to Greek interpretations of neoliberal policies and processes because of its centrality to Greek culture and identity. Food has also been a site of contested practices of "solidarity" and "charity" by which new social experiments are emerging in the wake of the breakdown of the welfare state. In arguing for food's centrality in the reshaping of Greek sociability, I will suggest that food be thought of not simply as a "topic" for anthropological investigation, but as a master-concept on the level of "kinship," "ritual," or "exchange" in any anthropological analysis of contemporary life.
Keywords: Greece; Greek crisis; Kalymnos; Oriental and African Studies; austerity (economics); critical food studies; food metaphors; food studies; kinship; neoliberalism; solidarity